Comparison of privacy consciousness between Japanese and Taiwanese. Issue 4 (3rd September 2018) - Tabata, Naoya; Sato, Hirotsune; Ninomiya, Katsumi; Yamamoto, Chika
Abstract: This study compared privacy consciousness between Japanese ( n  = 211) and Taiwanese ( n  = 308) high school students, who responded to the Privacy Consciousness Scale. Results indicated that Taiwanese students had higher privacy consciousness for the self and others than Japanese students.